The project RRC: A partnership based on action research - Sousa, Francisco (2012)
For the past five years the University of the Azores has worked with schools of elementary and secondary education from this Portuguese Autonomous Region in a partnership based on a project of collaborative research on curriculum. The project RRC (Researching for a Relevant Curriculum) has addressed teachers' worries about the lack of interest shown by some of their students with regard to the school and the curriculum. Accordingly, successive cycles of action research have been carried out by a team that includes university scholars and teachers from those schools. Data has been collected mainly through classroom field notes that provide evidence of given students' lack of interest, and through interviews with them. Each action research cycle is one school year long. Data have been analyzed and interpreted both individually and collectively. Such interpretation of data has inspired teachers in designing new teaching strategies, which have been continuously monitored and reviewed. The project has generated not only improvements in the students' acknowledgment of curriculum relevance but also some changes in the teachers' approach to their work, especially an increased sense of ownership of the curriculum and the adoption, to some extent, of research as a means of curriculum innovation.